The Quantitative Research of Interaction between Key Parameters and the Effects on Mechanical Property in FDM. (20th November 2017) - Li, Hongbin; Wang, Taiyong; Yu, Zhiqiang
Abstract : The central composite design (CCD) experiment is conducted to evaluate the interaction between parameters and the effect on mechanical property. The layer thickness, deposition velocity, and air gap are considered as the key factors. Three disparate levels of the parameters are utilized in the experiment. The experimental results suggest that all these parameters can affect the bonding degree of the filaments, which affects the final tensile strength of the specimen. A new numerical model is built to describe the cooling process of the fused filament, which shows a perfect coherence with the practical temperature file of filament. It reveals what the forming mechanism of the bonding between filaments is and how these parameters act on final tensile strength of the specimen of this way from temperature. It is concluded that the parameters are not working alone; in fact they all contribute to determining the mechanical property, while the air gap plays the predominant role in determining the final tensile strength, followed by layer thickness as the next predominant factor, and the effect of deposition velocity is the weakest factor.